Research Trends in Multidisciplinary Research (Volume-1) - Salunke, Sanjeev; Prabhakar.K; Kumar M (AG Volumes, 2025)
Research Trends in Multidisciplinary Research (Volume-1) is a comprehensive compilation of cutting-edge studies exploring the convergence of various academic fields. This volume showcases research spanning engineering, social sciences, health sciences, education, management, and more—highlighting the interconnectedness of diverse disciplines in solving real-world problems. The book is structured to provide readers with a broad perspective on current trends, methodologies, and innovations in multidisciplinary research. Each chapter offers valuable insights, backed by empirical data and critical analysis, catering to scholars, professionals, and students alike. By emphasizing the importance of collaborative and cross-disciplinary approaches, this book seeks to foster a deeper understanding of how integrated research enhances problem-solving and innovation. Whether for academic inquiry, professional development, or policy formulation, this volume serves as a timely reference for those committed to advancing knowledge through multidimensional research efforts.